315 An asset-based approach to advance minoritized patients’ participation in clinical research: Leveraging the expertise of experienced Black clinical research participants - De Sha Wolf (Journal of Clinical and Translational Science)
Objectives/Goals: To present an asset-based approach to advance minoritized patients’ participation in clinical research by elevating experienced Black research participants’ motivations and decision-making processes, favorable sociocultural research contexts, and impactful research questions to reduce chronic disease burden and improve quality of life. Methods/Study Population: Data will be extracted from a pilot study to develop an asset-based approach to clinical research with young Black adults living with chronic pain. Participants will be Black patients at an academic medical institution on the West Coast, ages 21 to 44, currently or formerly have chronic pain, and current or previous electronic health record-captured enrollment in a clinical research study. Approximately 25 Black patients will participate in semi-structured focus groups with topics including: motivations for research participation, access to research, preferred research activities, perceived research benefits, favorable structural and cultural contexts, considerations of past ethical and trust violations, and alignment of research questions and patient needs. Data will be collected Fall ‘24 and analyzed in Winter ‘25. Results/Anticipated Results: We will examine experienced Black clinical research participants’ decision-making processes for participating in research, including access to studies, perceived value of research, community support, and alignment of study goals with their personal interests and needs. Results will illuminate the sociocultural, structural, and historical contexts under which Black patients have successfully participated in clinical research, and types of studies they have participated in, and recruitment procedures that have been effective. Also, we will examine the conditions for successful study completion. Investigators will also learn about the types of clinical research questions that minoritized patients believe will have an immediate and long term impact on their lived experienced with chronic illness. Discussion/Significance of Impact: The results will challenge deficit models of minority research participation that focus solely on barriers to participation, previous ethical harms, and violations of trust/trustworthiness by elevating the motivations, favorable contexts, and empirical priorities of experienced Black clinical research participants.